16th International Conference on Evaluation &Amp; Assessment in Software Engineering (EASE 2012) 2012
DOI: 10.1049/ic.2012.0035
|View full text |Cite
|
Sign up to set email alerts
|

A mapping study of software code cloning

Abstract: Background: Software Code Cloning is widely used by developers to produce code in which they have confidence and which reduces development costs and improves the software quality. However, Fowler and Beck suggest that the maintenance of clones may lead to defects and therefore clones should be re-factored out. Objective: We investigate the purpose of code cloning, the detection techniques developed and the datasets used in software code cloning studies between the years of 2007 and 2011. This is to analyse the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For example, Ain et al [1] focus on code clone detection methods, the related data, and intermediate data representations involved in the methods. Although there are related works that focus on sub-research area classification and popularity analysis [5,12,47,51,53,63], these works either focus on a specific sub-research area, e.g., software similarity [5],…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ain et al [1] focus on code clone detection methods, the related data, and intermediate data representations involved in the methods. Although there are related works that focus on sub-research area classification and popularity analysis [5,12,47,51,53,63], these works either focus on a specific sub-research area, e.g., software similarity [5],…”
Section: Introductionmentioning
confidence: 99%
“…or the research area has broadened. The popularity may change after a long time of development [47,51,53,63], Or there is a lack of analysis of the development trend of sub-research areas [12]. At the same time, we found that the classification of code cloning in the relevant studies was based on research experience.…”
Section: Introductionmentioning
confidence: 99%